العالم الإسلامي: عوامل القوة وأسباب الضعف؛ دراسة تحليلية في ضوء السياسة الشرعية: The Muslim World: Factors of Strength and Causes of Weakness; An Analytical Study Based on Islamic Politics - Dafer Humood Al-Sheheri; Amer Abdulwahab Mahyoub Murshed (Journal Al-Muqaddimah, 2024)
The study aimed at identifying the factors of strength in the Islamic world and determining the causes of its weakness in the contemporary reality. The problem of the study lies in the weakness that the Islamic world suffers in the contemporary reality because of several reasons that have caused Muslims’ weakness and the delay of the Islamic world in the civilizational competition, although it has the inherent factors of strength qualifying it for leadership and pioneer ship. The study adopted the inductive analytical methodology due to its suitability to the study nature and its ability to realize its goals. The study revealed several key findings, the most important of which is that the Islamic world is not a barren place without vegetation or water. Rather, it is located at the world’s center, holding its borders, controlling its oceans, seas, and navigation routes, and is rich with major rivers, the most fertile lands, and the greatest wealth, which makes it commercially, economically, and militarily important. The potential strengths of the Islamic world include the Islamic unity based on creed and the brotherhood of religion, the availability of natural and human resources. The main causes of the Islamic world’s weakness include intellectual invasion, plans to divide the Islamic world, and weakening the Islamic world in the areas of economy, politics, and security. The researcher recommends unifying Islamic efforts to achieve economic integration that allows the exchange of resources, expertise, goods, and products, and establishing unified Arab Islamic markets, and necessarily creating an Islamic alliance or bloc like the European Union that permits industrial and commercial exchange among all Islamic countries.